Five Key Ideas to Teach Fractions and Decimals with Understanding - Brendefur, Jonathan (Advances in Social Sciences Research Journal, 2016)
The teaching of fractions and decimals is a significant challenge for many teachers due to the inherent difficulty of the topic for students as well as the lack of high-quality, modernized curricular materials. This article examines the key ideas of teaching fractions and decimals for understanding that are evident in the current research literature and the curricular materials and teaching strategies from high-achieving nations.